The conservation of heritage sites in peninsular Malaysia: reformation of the legal framework / Azni Mohd Dian - Mohd Dian, Azni (Institute of Graduate Studies, UiTM, 2018)
The issue of destruction of heritage site over the decades is still an unresolved subject until to date. After the introduction of Act 645, the public is expecting that it will be a forceful arrangement to preserve the heritage site from the intentional and uncontrollable destruction activities. Nevertheless, various reasons have been identified as the influential factors that contribute to such problems; lack of coordination between the heritage administrative bodies, broad discretionary powers of the Commissioner of Heritage and the Minister of Tourism and Culture in the designation and administration of heritage site conservation; and lack of empowerment of the people in both the heritage and planning legal frameworks. The objectives of this research are to examine the extent of coordination among the heritage administration bodies underlined by the present legal framework; to compare such legal framework with other similar legal instruments applied by some selected countries in identifying the strengths and weaknesses in the heritage site management; and consequently, to propose for a more holistic and feasible form of legal framework in Malaysia. This research adopts a qualitative method by conducting a library-based research to scrutinise the shortcomings of the National Heritage Act 2005, Town and Country Planning Act 1976, Environment Quality Act 1974, and selected state heritage enactments i.e. the Malacca Preservation and Conservation of Cultural Heritage Enactment 1988 and the State of Penang Heritage Enactment 2011. Interviews are conducted to retrieve information from the public officials in the federal and state heritage and planning departments, land registries and chosen heritage NGOs in Melaka and Penang. The theoretical framework is examined to understand the extent of public participation in the designation of a heritage site and its conservation management process. The states of Melaka and Penang are the primary case studies in this thesis. While in a contemporary era, a participatory democracy which is deemed significant to promote the idea of common good, its absence in a social and cultural perspective is evident in the preservation and heritage planning literature. Ultimately, it raised philosophical problems of selectivity, authenticity, interpretation, and recreation of the cultural heritage development. Among the issues discovered in this study are different preferences regarding what is worthy of conservation; the lack of an efficient public participation mechanism; lack of an integrated heritage conservation approach in the planning and environmental decision-making process; the different and conflicting interests of various stakeholders; power disparity; mobilisation of interest groups; and the lack of knowledge on heritage conservation. It is recommended that the integration of the powers and role of the Heritage Council and other relevant heritage administrative bodies are reinforced while the empowerment of the people is enhanced via the heritage site nomination, planning development, awareness, and education processes. As both land use planning development and heritage sites conservation processes have a common goal, that is, to promote sustainable development, they can be brought together in a common philosophy and practice.